2017
DOI: 10.5455/njppp.2017.7.0516622052017
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical assessment of the hepatic functions of the petrol pump workers of Jaipur city

Abstract: Background: In recent years, occupational health hazards have grown as one of the major public health issues worldwide. In this context, petrol pump workers were studied who by virtue of their occupation is continuously exposed to the various chemical substances and volatile organic compounds liberated in the form of gasoline vapors in their breathing zone. Aims and Objectives: To explore the effects of gasoline vapors on some biochemical parameters (the liver enzymes) among the petrol pump filling attendants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…In contrast, higher serum transaminase activities were observed among fuel-filling workers of Sulaimani city compared to the controls, though these values were within the normal range for clinical diagnosis of hepatic injury (27). Furthermore, significantly higher liver enzymes among petrol filling attendees in comparison to controls have been reported in several studies (12,14,15,24,26).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In contrast, higher serum transaminase activities were observed among fuel-filling workers of Sulaimani city compared to the controls, though these values were within the normal range for clinical diagnosis of hepatic injury (27). Furthermore, significantly higher liver enzymes among petrol filling attendees in comparison to controls have been reported in several studies (12,14,15,24,26).…”
Section: Discussionmentioning
confidence: 74%
“…In addition, it is in agreement with the findings among petrol station attendants in Nigeria and volatile substance abusing street children in Turkey (22, 23). On the other hand, Gupta et al (24) found that ALP activity was non-significantly higher in petrol filling attendants. The increase in ALP activity generally originates from the hepatobiliary system.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[24][25][26][27][28] Besides, PDS attendants are responsible for unloading petroleum products from supply tankers into PDS underground reservoirs and take daily stock of dispensed petroleum products from PDS reservoirs. 29 PDS attendants chronically exposed to PPF fractions, and their by-products, mainly by inhalation of volatile fractions 30 and dermal contact during a regular workday (8-10 hours). Besides, PDS attendants are exposed regularly to exhaust fumes from vehicles procuring petroleum products from dispensing stations.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic occupational exposure to PPF constituent is primarily detrimental to human health, 20‐23 which can be further exacerbated by the absence of enforceable occupational safety regulation, inadequate personnel safety equipment, and unsafe work conditions 24‐28 . Besides, PDS attendants are responsible for unloading petroleum products from supply tankers into PDS underground reservoirs and take daily stock of dispensed petroleum products from PDS reservoirs 29 . PDS attendants chronically exposed to PPF fractions, and their by‐products, mainly by inhalation of volatile fractions 30 and dermal contact during a regular workday (8‐10 hours).…”
Section: Introductionmentioning
confidence: 99%